Principles of Direct, Database and Digital Marketing - Tapp, Alan; Whitten, Ian; Housden, Matthew (Pearson International Content, 2014)
The growth of digital marketing is the most important yet unpredictable trend in marketing today. How can the online world be harnessed by the companies of today and tomorrow to grow their marketing impact? What role do information and databases have to play in this system? And why do some non-digital means of direct marketing still remain so powerful?   Alan Tapp’s successful text has long been a leading authority on direct marketing, and for this edition he is joined by Ian Whitten and Matthew Housden. The authors all bring great expertise across direct, database and digital marketing to provide comprehensive, compelling coverage of the key theory and debates of the fields.   The 5th edition includes comprehensive coverage of all recent developments in digital marketing, including analysis of the seemingly relentless rise of Facebook, Twitter and other forms of social media. It has a range of thoroughly updated case studies covering companies and organisations from sports teams to car manufacturers and non-profits and contains a new chapter on Data Protection legislation and its impact on marketers.    The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.